Modeling the threshold voltage of PNIN SSOI tunnel field‐effect transistor. (1st September 2015) - Li, Yuchen; Liu, Shulin; Tong, Jun; Zhang, Yan
Abstract: In this paper, a physically based analytical threshold voltage model for PNIN strained‐silicon‐on‐insulator tunnel field‐effect transistor (PNIN SSOI TFET) is proposed by solving the two‐dimensional (2D) Poisson equation in narrow N + layer and intrinsic region. In the proposed model, the effect of strain (in terms of equivalent Ge mole fraction), narrow N + layer and gate dielectric, and so on, is being considered. The validity of the proposed model is verified by comparing the model results with 2D device simulation results. It is demonstrated that the proposed model can correctly predicts the trends in threshold voltage with varying the device parameters. This proposed model can be effectively used to design, simulate, and fabricate the PNIN SSOI TFETs with the desired performance. Copyright © 2015 John Wiley & Sons, Ltd.